A roadmap for sustainably governing the global antimicrobial commons - Rogers Van Katwyk, S; Balasegaram, M; Boriello, S; Farrar, J; Giubilini, A; Harrison, M; Kieny, M; Kirchhelle, C; Liu, J; Outterson, K; Pate, M; Poirier, M; et al. (Elsevier, 2019)
Antimicrobials are needed to treat deadly infections, enable life-saving medical procedures, and manage disease in food production. But antimicrobials come with a trade-off: their use accelerates antimicrobial resistance (AMR), which diminishes the future effectiveness of these medicines. This trade-off makes “antimicrobial effectiveness” a precious global common-pool resource that must be collectively protected. 1 Yet antimicrobials have been used inappropriately for decades. In too many circumstances, antimicrobials are deployed to compensate for inadequate infection prevention and control (IPC) in both human health and food production, instead of implementing water, sanitation, and hygiene (WASH) and IPC measures such as preventing hospital overcrowding and ensuring good equipment sterilisation practices. 2 In the process, this precious resource has been jeopardised. 3 , 4